Assessment of Secondary Markets for Movable Assets in the Jamaica Manufacturing Sector - International Finance Corporation (International Finance Corporation, Washington, DC, 2020)
One of the critical challenges to micro, small, and medium enterprises (MSMEs) continues to be access to finance (World Bank 2019). Asset-based lending (ABL) is emerging as a unique financing option for businesses and a new way to provide working-capital financing to support business growth and sustain business operations. The approach leverages nontraditional but valuable movable assets such as machinery, equipment, securities, accounts receivable, agricultural produce, and intellectual property rights as collateral to secure financing from credit institutions. These assets are common among entrepreneurs and established businesses but are seldom considered as a useful form of collateral to access short-term financing. Interestingly, among developing countries, movable assets represent as much as 78 percent of the capital stock of enterprises relative to immovable assets such as land and buildings (22 percent) (Alvarez de la Campa 2011). Despite this, insufficient collateral continues to be one of the main reasons loans are not granted in emerging markets (Fleisig, Safavian, and de la Pena 2006), perhaps reflecting the preference of financial institutions to utilize collateral based on immovable assets such as land and buildings. This assessment seeks to examine MABL in Jamaica, with a focus on developing possible options for deepening secondary markets among assets commonly used as collateral in MABL. The report includes recommendations for developing secondary markets, among other potential assets that can be used for MABL, as well as general steps for implementation.